Loss of P16 in Esophageal Adenocarcinoma Detected by Fluorescence in situ Hybridization and Immunohistochemistry - Kotzev A. (Sciendo, 2017)
Molecular biology of esophageal adenocarcinoma (EAC) is not fully elucidated. The aim of this study was to assess the expression of cycle regulator and tumor suppressor p16 in esophageal adenocarcinoma. The expression of p16 at protein and gene level was investigated using immunohistochemistry and fluorescence in situ hybridization in thirteen EAC specimens obtained by endoscopic biopsies and surgical resections. The mean age of enrolled patients was 62 years and a male predominance was observed. Loss of p16 protein expression was detected in 77% of the cases and loss of p16 gene was found in 69% of cases as hemizygous deletion was the most common. Significant correlation was found between the absence of p16 protein expression and p16 allelic loss. Cell cycle disturbances seem to play role in the EAC carcinogenesis and probably p16 gene deletions are connected with the loss of p16 protein expression.